Development of an international survey tool to measure confidence and current antimicrobial stewardship practices of hospital pharmacists. (13th October 2022) - Weier, Naomi; Thilly, Nathalie; Howard, Philip; Demore, Béatrice; Patel, Rahul; Pulcini, Céline; Zaidi, Syed Tabish R
Abstract: Background: Pharmacists are identified as key members of hospital antimicrobial stewardship (AMS) teams in international guidelines. Developing an international standardized tool to measure hospital pharmacists' confidence and practices of AMS will encourage knowledge sharing and better networking between hospital pharmacists internationally. Objectives: To develop a survey tool that can be used internationally to assess pharmacists' knowledge, confidence, perceived barriers and current AMS practices. Methods: A project team was formed to refine the survey tool that was initially used in a previous survey study. Following revision by the project team, a revised survey tool was sent to the ESCMID Study Group for Antimicrobial Stewardship (ESGAP). Feedback from the ESGAP members was considered by the project team to finalize the survey tool. Results: A total of 88 changes were made to the survey tool after revision by the project team. A total of 43/216 (19.9%) of ESGAP members provided feedback on the survey tool, which led to a further 19 revisions. ESGAP members were agreeable to the questions in the survey tool, with >50% agreeing that each question was suitable. The final survey tool consisted of 42 questions, reduced from 72 questions in the original survey. Conclusions: An international survey tool to measure hospital pharmacists' confidence and practices of AMS was developed. This tool will help the wider hospital pharmacy community in conducting local studies on current AMS practices and to identify areas where further support is needed. Use of a standardized survey tool will also allow individual regions/countries to compare their data with other countries to identify potential quality improvement programmes.